Habitat Use in a Depleted Population of Winter Flounder: Insights into Impediments to Population Recovery. Issue 6 (30th September 2016) - Howell, Penelope T.; Pereira, Jose J.; Schultz, Eric T.; Auster, Peter J.
Abstract: The distribution and demographics of a population of Winter Flounder Pseudopleuronectes americanus were examined for changes related to habitat quality over a fishery‐independent survey period of 29 years, encompassing an 82% decline in abundance. We tested for spatial and temporal variation in indicators of fitness to determine whether they revealed likely processes that resulted in the observed patterns of habitat use. We also assessed temporal changes in fitness and inferred changes in habitat quality associated with population decline. We focused on the condition of postspawn (resting) mature and immature fish of both sexes during a critical period of spring feeding prior to summer migration. Analysis of variance of individual condition indices (log10 [length]–log10 [weight] regression residuals) by sex/maturity group and time period identified consistent and significant differences among six survey strata. Highest condition indices were observed for fish that were captured in shallow (<18‐m) mud, sand, and transitional bottom sediment and deep (>18‐m) mud areas, collectively classified as high‐quality habitat. The proportion of the population that occupied high‐quality habitat remained unchanged at approximately 60% over the time series. As abundance decreased, condition decreased in mature females, increased in immature fish of both sexes, and was mixed in mature males. Additionally, the proportion mature at length shifted significantly upward for both sexes, the back‐calculated lengths at ages 2 and 3 increased for mature individuals, and the estimated winter growth declined for age‐3 mature and immature females. The results suggested increased competition for prey among mature fish and increased predation pressure on smaller fish. This Winter Flounder population may be responding to an increase in the abundance of competing mid‐Atlantic species, which was brought about by increasing water temperature. These second‐order effects may have chronically hindered Winter Flounder reproduction and therefore stock rebuilding, especially in areas of low‐quality habitat. Received September 23, 2015; accepted July 18, 2016 Published online September 30, 2016